HUBUNGAN GAYA HIDUP DENGAN TEKANAN DARAH PADA LANSIA DI WILAYAH KERJA PUSKESMAS KENDALKEREP KOTA MALANG - Revanda Rera Amelia; Joko Wiyono; Naya Ernawati; Suprajitno Suprajitno (Poltekkes Kemenkes Malang, 2025)
High blood pressure is a cardiovascular syndrome characterized by increased arterial blood pressure which often occurs in the elderly. An unhealthy lifestyle will worsen the health condition of the elderly, especially regarding their blood pressure. The aim of this research is to determine the relationship between lifestyle and blood pressure in the elderly in the Kendalkerep Community Health Center Working Area, Malang City. This research uses a correlative design with a cross sectional study approach. The sample in this study was all 80 elderly people >60 years old who were selected using purposive sampling techniques. Data collection was carried out using a lifestyle questionnaire. The data analysis method uses univariate and bivariate analysis. Bivariate analysis in this study used the Spearman Rank correlation test. The results of the research show that there is a relationship between lifestyle (physical activity p value = 0.000, diet p value = 0.000, resting habits p value = 0.000, smoking habits p value = 0.027, caffeine consumption habits p value = 0.001) and blood pressure. An unhealthy lifestyle can cause an increase in blood pressure, especially in the elderly. It is recommended that seniors always follow good lifestyle recommendations such as sufficient physical activity, avoiding excessive consumption of salt, coconut milk and fat, getting enough rest, reducing smoking and caffeine consumption. Keywords: Lifestyle, Blood Pressure, Elderly